2019
DOI: 10.1103/physrevb.100.125156
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric control of topological phases in graphene

Abstract: Topological antiferromagnetic (AFM) spintronics is an emerging field of research, which involves the topological electronic states coupled to the AFM order parameter known as the Néel vector. The control of these states is envisioned through manipulation of the Néel vector by spin-orbit torques driven by electric currents. Here we propose a different approach favorable for low-power AFM spintronics, where the control of the topological states in a two-dimensional material, such as graphene, is performed via th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…The spin signal is also found to persist well beyond T N , where any boundary magnetism should be lost, remaining visible at the highest studied temperature of ≈450 K. These observations are consistent with the results of prior theoretical work, which predict that chromia breaks the crystal symmetry of graphene (from C 6v to C 3v ) and generates an effective SOC term of ≈40 meV. [ 25,26,41 ] As such, our observations point to the suitability of chromia/graphene heterostructures for use in spintronic devices, capable of operation at room temperature and beyond. [ 26,42 ] This should be contrasted with prior studies of proximity effects in graphene/AFM heterolayers; [ 24,43–45 ] while some of these works [ 24,45 ] have established the presence of very large exchange coupling between the layers, this situation is only realized for temperatures below T N .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The spin signal is also found to persist well beyond T N , where any boundary magnetism should be lost, remaining visible at the highest studied temperature of ≈450 K. These observations are consistent with the results of prior theoretical work, which predict that chromia breaks the crystal symmetry of graphene (from C 6v to C 3v ) and generates an effective SOC term of ≈40 meV. [ 25,26,41 ] As such, our observations point to the suitability of chromia/graphene heterostructures for use in spintronic devices, capable of operation at room temperature and beyond. [ 26,42 ] This should be contrasted with prior studies of proximity effects in graphene/AFM heterolayers; [ 24,43–45 ] while some of these works [ 24,45 ] have established the presence of very large exchange coupling between the layers, this situation is only realized for temperatures below T N .…”
Section: Introductionsupporting
confidence: 89%
“…This is precisely the behavior expected for the spin-Hall signal, whose magnitude is inversely proportional to the charge conductivity of graphene, [52] and points to the presence of extrinsic SOC that arises from the contact with chromia. [41] To allow comparison with the magnitude of R nl , in Figure 2a we also plot the corresponding variation of the ohmic resistance (R Ohmic ). This latter quantity is essentially the resistance that should be measured at the non-local probes due to leakage of classical current lines from the local measurement setup [20,24,[53][54][55] ln cosh 1…”
Section: Resultsmentioning
confidence: 99%
“…Interfacial coupling is known to affect the QHE in graphene, usually in two different ways: charge impurities that cause a reduced mobility yet a wider quantum Hall (QH) plateaux in some circumstances 6 , and charge transfer that, to some extent, shifts the effective doping [11][12][13][14][15][16] . Theories predict that the interplay between an antiferromagnetic insulator and graphene can give rise to topological quantum ground states, such as quantum anomalous Hall phases [17][18][19] . Experimentally, RuCl 3 /graphene is, indeed, spotted with a strong charge transfer, which is sometimes possibly coupled to the magnetism 20 and sometimes not fully evidenced so 21 .…”
mentioning
confidence: 99%
“…The exchange coupling between Cr 2 O 3 and Ag 2 Te across the interface in the Ag 2 Te/Cr 2 O 3 structure is mediated by the surface magnetization through the proximity effect. The recent work has shown that a topological phase of graphene can be tuned by magnetization orientation in a graphene/Cr 2 O 3 system 38 . Figure 3a shows the atomic structure (produced using the VESTA software 39 ) of the Ag 2 Te/Cr 2 O 3 (0001) system consisting of monolayer Ag 2 Te and Cr 2 O 3 substrate composed of 6 and 12 atomic layers of O and Cr, respectively.…”
Section: Electrical Conductivity and Anomalous Hall Conductivitymentioning
confidence: 99%